SERVQUAL Questionnaire based Health Service Quality Assessment in a Private Hospital of Western Nepal. - Ghimire, Pradeep; Ghimire, Prajwal; Acharya, Madhu (Nepal Journal of Medical Sciences, 2020)
Introduction: Questionnaire based assessment is a simple, scientific tool to collect responses from individuals and standardised questionnaires can be used to assess health care quality of a health care institution. The aim of this study was to assess health service quality of a private hospital on the basis of questionnaire-based data collected from the patients admitted in the hospital using service quality (SERVQUAL) questionnaire method. Methods: A descriptive cross sectional study was conducted in 203 adult patients in Fishtail Hospital and Research Centre, Pokhara, Nepal from January 2015 to January 2016. The response of the patients towards various aspects of service provided by the hospital was collected using SERVQUAL questionnaire. The data was graded in Likert scale and SPSS software 24 was utilized to analyse the data. Results: A total of 181(89.12%) patients were satisfied with the health service quality provided by the hospital that was assessed on the basis of parameters of SERVQUAL questionnaire and 156 (76.74%) patients graded various hospital factors as being good. Conclusions: Based on SERVQUAL questionnaire we found that 89.12% of patients were satisfied with the service provided by our hospital and 76.74% of patients graded various hospital factors such as doctors, nurses, reception staff and food provided in canteen as being good. We recommend such surveys should be regularly performed in health care institutions to scrutinise and enhance the level of health care service quality.